2021
DOI: 10.3390/microorganisms9091941
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Prolonged Hospital Length of Stay in Adults with Imported Falciparum Malaria—An Observational Study from a Tertiary Care University Hospital in Berlin, Germany

Abstract: Outcome of falciparum malaria is largely influenced by the standard of care provided, which in turn depends on the available medical resources. Worldwide, the COVID-19 pandemic has had a major impact on the availability of these resources, even in resource-rich healthcare systems such as Germany’s. The present study aimed to determine the under-explored factors associated with hospital length of stay (LOS) in imported falciparum malaria to identify potential targets for improving management. This retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…We found LOS significantly shorter than the 7 days reported under trial conditions in South East Asia 13 and slightly longer than the 3 days LOS reported in a retrospective observational study from a tertiary hospital setting in Germany. 14 The reported LOS differences between studies likely reflect the severity specifics of the studied malaria populations ranging from exclusively focused severe malaria patients in Southeast Asia 13 over a quarter of severe malaria cases estimated in our study to only 10% of severe cases included in the malaria sample in Germany. 14 …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We found LOS significantly shorter than the 7 days reported under trial conditions in South East Asia 13 and slightly longer than the 3 days LOS reported in a retrospective observational study from a tertiary hospital setting in Germany. 14 The reported LOS differences between studies likely reflect the severity specifics of the studied malaria populations ranging from exclusively focused severe malaria patients in Southeast Asia 13 over a quarter of severe malaria cases estimated in our study to only 10% of severe cases included in the malaria sample in Germany. 14 …”
Section: Discussionmentioning
confidence: 74%
“… 14 The reported LOS differences between studies likely reflect the severity specifics of the studied malaria populations ranging from exclusively focused severe malaria patients in Southeast Asia 13 over a quarter of severe malaria cases estimated in our study to only 10% of severe cases included in the malaria sample in Germany. 14 …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Also, discharge criteria might be varied, depending on bed requirement situation. During COVID-19 outbreak, stress on bed availability occurs and might affect standard of care 2 . Length of hospital stay not only for COVID-19 but also for other infectious disease might have to be shortened 2 .…”
mentioning
confidence: 99%
“…During COVID-19 outbreak, stress on bed availability occurs and might affect standard of care 2 . Length of hospital stay not only for COVID-19 but also for other infectious disease might have to be shortened 2 . Therefore, data on length of stay might be easily biased.…”
mentioning
confidence: 99%